Mechanical Vibration - A quick and EfficienMethod of Removing Damaged Prosthesis from its Cemented Position (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Implant replacement or revision surgery in thehuman body ranks among the most demanding surgeries that orthopedic surgeons encounter in modern medicine.The removal of the hardened bone cement which securesthe implant within the bone, is the cause of a lengthyoperation. Often the use of sharp surgical instruments,ultrasonic devices etc. are employed, however all thesemethods are time-consuming and present variouscomplications.This paper describes the use of mechanical vibrations at afrequency of 40 Hz, on samples of implants anchored inanimal (pig) bone cavities with bone cement. Using a rotaryhammer drill equipped with a specially designed adaptor, toengage the tip of the implant, good results were obtained.The implant with its cement mantle was removed in a shorttime not exceeding 22 seconds.The procedure appears to be safe and is accomplished ina short time, commensurate with what is required inrevision surgery.